1995
DOI: 10.1111/j.1432-1033.1995.152_1.x
|View full text |Cite
|
Sign up to set email alerts
|

The Structure of the Lipid A‐Core Region of the Lipopolysaccharides from Vibrio cholerae O1 Smooth Strain 569B (Inaba) and Rough Mutant Strain 95R (Ogawa)

Abstract: The lipopolysaccharides (LPS) from Vibrio cholerae 9SR, a rough mutant strain of 01 I ! cholerae 162 (Ogawa), and from smooth 0 1 I ! cholerae 569B (Inaba) were de-0-acylated. In each case, one part of the products was treated with 48% aqueous HF which removed the phosphoryl and fructose residues, then reduced, de-N-acylated, and N-acetylated. Another part was de-N-acylated by treatment with hot KOH. The products of both degradation pathways were separated by high-performance anion-exchange chromatography. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
38
0

Year Published

1999
1999
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(43 citation statements)
references
References 19 publications
5
38
0
Order By: Relevance
“…Electrospray mass spectrometry of pool I gave a molecular ion at m\z l 1650, consistent with the structure proposed for the core of V. cholerae O1 LPS (Vinogradov et al, 1995) (Fig. 5).…”
Section: Characterization Of Lpss and Derived Fragmentssupporting
confidence: 50%
See 1 more Smart Citation
“…Electrospray mass spectrometry of pool I gave a molecular ion at m\z l 1650, consistent with the structure proposed for the core of V. cholerae O1 LPS (Vinogradov et al, 1995) (Fig. 5).…”
Section: Characterization Of Lpss and Derived Fragmentssupporting
confidence: 50%
“…α--mannopyranosyl residues] is resistant (Kenne et al, 1982 ;Vinogradov et al, 1995 ;Wang et al, 1998).…”
Section: Methodsmentioning
confidence: 99%
“…LPS was purified by aqueous phenol extraction and ultracentrifugation from killed cells, as described by Vinogradov et al (1995), with modifications. The bacteria were scraped off BHIBC agar into PBS, and following phenol extraction, 4 vols distilled water was added and the mixture dialysed with tap water until no phenol odour remained.…”
Section: Methodsmentioning
confidence: 99%
“…1A and B). For the core OS of serogroups O1, O139, and O22 it was found that one D-fructose is linked to the D-glucose residue on HepI (15,16,37,38,68), while in the H11 isolate D-sedoheptulose is found instead at the same position (7,68). Other basic differences between the O1, O139, and O22 core OS and the H11 core OS are the presence of a terminal hepto-FIG.…”
mentioning
confidence: 99%